The Impact of Board Characteristics and Audit Committee on Tax Avoidance: Empirical Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange in 2021–2023 - Putri, Dwi Nika; Kartika, Indri (Journal of Advanced Multidisciplinary Research, 2025)
Tax avoidance is a common strategy used by companies to reduce their tax burden, which may affect government revenue and reflect the effectiveness of corporate governance. In this context, the role of the board of commissioners and the audit committee is crucial in supervising management decisions related to tax planning. Several studies have investigated the effect of corporate governance mechanisms on tax avoidance, but there is limited evidence regarding specific board characteristics such as gender diversity and meeting frequency. This study aims to examine the influence of board size, board independence, board meeting frequency, board gender diversity, and the audit committee on tax avoidance. The sample of this research consisted of 100 observations from manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period, selected through purposive sampling. The data were analyzed using Multiple Linear Regression Analysis. The results show that board independence and board gender diversity have a negative and significant effect on tax avoidance, while the audit committee has a positive and significant effect. Meanwhile, board size and board meeting frequency do not have a significant effect. These findings suggest that a stronger presence of independent and female commissioners contributes to more transparent and compliant tax behavior.